2021
DOI: 10.1039/d0ta10565a
|View full text |Cite
|
Sign up to set email alerts
|

Hydronium ion diffusion in model proton exchange membranes at low hydration: insights from ab initio molecular dynamics

Abstract: Sequence of steps in the reaction of hydronium (H3O+) with sulfonate (SO3−) contributing to the proton structural diffusion mechanism in a low-hydration environment of a proton-exchange-membrane (PEM) mimic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(71 citation statements)
references
References 88 publications
2
69
0
Order By: Relevance
“…Based on the results presented in Section 4.3.1 and combined with inspection of configurations from the AIMD trajectory, we propose, in Figure 8, an idealized diffusion mechanism for hydronium ions in the PEM model under idealized hydration conditions (λ = 3) [55]. First, the hydronium ion is located in the center of the cell, solvated by three water molecules (Figure 8a).…”
Section: H 3 O + Diffusion Mechanismmentioning
confidence: 82%
See 4 more Smart Citations
“…Based on the results presented in Section 4.3.1 and combined with inspection of configurations from the AIMD trajectory, we propose, in Figure 8, an idealized diffusion mechanism for hydronium ions in the PEM model under idealized hydration conditions (λ = 3) [55]. First, the hydronium ion is located in the center of the cell, solvated by three water molecules (Figure 8a).…”
Section: H 3 O + Diffusion Mechanismmentioning
confidence: 82%
“…Dispersion forces were accounted for using the Dispersion-Corrected Atomic Core Pseudopotential (DCACP) scheme [61,62] within the Kohn-Sham formulation of Density Functional Theory using the B-LYP exchange-correlation functional [63,64]. The B-LYP+DCACP has been selected for this study, as it has previously been shown to produce satisfactory results for water-acene interactions [65], liquid water [66], and hydronium diffusion in bulk water [38][39][40]67] A detailed description of the construction of the initial structures and of the computational methodology can be found in the Supplementary Information (SI) and in References [52][53][54][55].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations